A Unique Association of Recurrent Swollen Lymph Nodes and Sweet Products in Pediatrics: A Cross Sectional Analysis in Rural Population of KPK - Umair Farukh, Zain Ul Abideen, Sheherbano Yahya, Ramsha Khan, Owais Qaisar, Zia Ul Arifeen, Iftikhar Ahmad, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The current study was aimed to investigate the association of dental caries with sweet products (especially sweetened milk at night) with lympha- denopathy in pediatrics. There is a well established mechanism of sweets with dental caries, and such caries can be the cause of recurrent lymphadenopathy. Methodology: A total 201 patients were assessed at pediatric and dental clinic, patients of ages 1 to 5 years having recurrent lymphadenopathy and dental caries were included while the rest were excluded. They were evaluated for a number of parameters including dental caries grading, raised TLC, body temperature, pain, addiction towards sweets, hunger status, difficulty in chewing, sleep habits, social behavior, while their parents were interviewed regarding awareness about dental caries. Results: It was observed that 90% of the patients were addicted to sweets, and 79% were having grade 4 dental caries, 82% were having aggressive behavior, 91% were having pyrexia, 94% were having raised TLC, 75% were in severe pain, 88% were facing difficulty in chewing solid food, 61% were underweight, 58% were anorexic, while 98% of the parent were not having any proper knowledge about caries development. The practical implication of the study is to develop new strategies to minimize the consumption of sugary products that are the ultimate cause of dental caries. Such caries are then responsible for a number of issues including swollen lymph nodes. Conclusion: All these issues may have a worst impact on the social, physical and mental growth of children. As all the patients were having recurrent lymphadenitis, yet it can be claimed that dental caries are among the primary causes. Keywords: Dental caries; Lymphadenopathy; Pediatrics; Street sweets; Sweetened Milk.